The Life of Marine Engineer Officer Edgars Oto Pinka (1895–1941) - Zvirgzdiņš, Indulis (History of Engineering Sciences and Institutions of Higher Education, 2023)
Based on the documents, the study provides a wide and comprehensive evaluation of the life of an engineer and citizen from Vidzeme Edgars Otto Pinka (1895–1941). His life was related to ships, military service in Latvia, Russia, and France, and the Latvian Society of Paris. Researching E. O. Pinka’s studies and work, the author has studied the engineer’s life from birth to the end of his life, reflecting on his progress as one of the best specialists in the Latvian Navy in his capacity of an engineer mechanic, shipping engineer, officer, and pedagogue. The contribution of E. O. Pinka to raising awareness about Latvia and Latvian music in France in the early 1930s is also significant. His daughter, a graduate (1964) of Riga Polytechnic Institute (RPI) Māra Pinka, inherited his interest in music. The article was developed by studying the collections of Latvian libraries, archives, and museums and communicating with the successors of E. O. Pinka’s family.